DISPUTE ON LAND STATUS IN THE TRANSMIGRATION VILLAGE AREA IN AND AROUND THE FOREST AREA IN PURWOTANI VILLAGE LAMPUNG SELATAN - Wijonugroho, Pradipta; Akib, Muhammad; Tisnanta, HS; Sumarja, FX (Universitas Lampung, 2023)
One of the objectives of transmigration is to move people from one area to another in the context of population distribution and development. Transmigration participants will be given residential land and business land. The promised land for business often needs to be clarified or still has the status of forest land. Transmigrants are still facing the problem of obtaining business land so horizontal and vertical land disputes are often found in the province of Lampung. This study aims: first, to analyze government policies in resolving land status disputes in transmigration villages in Lampung Province. The type of research used is normative empirical with a statutory approach. Legal materials required by legislation, documents, and library materials. The data obtained were analyzed using qualitative methods. The results of the study show that the Government's Policy in Settlement of Transmigration Village Land Status Disputes in Lampung Province, especially in the Purwotani village area which is included in Register 40 Gedongwani is carried out through a community empowerment program in the form of a social forestry program which is in line with Presidential Regulation 88 of 2017 concerning the Settlement of Land Tenure in Forest Areas. The legal implication is that transmigrants do not get land ownership rights as business land but only use forest land (social forestry). It is recommended to the government considering that transmigrants control land business first then the determination of the Gedongwani Register 40 forest area, the government should release the forest area by changing the forest area boundaries and give it to transmigrants with land ownership rights, and not limited to social forestry.